Silybin and silymarin - new effects and applications - Kren, Vladimir; Walterova, Daniela (Biomedical papers, 2005)
This article aims to review critically literature published mainly within this millennium on the new and emerging applications of silymarin, the polyphenolic fraction from the seeds of Silybum marianum and its main component silybin. Silymarin and silybin used so far mostly as hepatoprotectants were shown to have other interesting activities as e.g., anticancer and canceroprotective. These activities were demonstrated in a large variety of illnesses of different organs as e.g., prostate, lungs, CNS, kidneys, pancreas and others. Besides the cytoprotective activity of silybin mediated by its antioxidative and radical-scavenging properties also new activities based on the specific receptor interaction were discovered - e.g., inhibition and modulation of drug transporters, P-glycoproteins, estrogenic receptors, nuclear receptors and some others. New derivatives of silybin open new ways to its therapeutic applications. Pharmacology dealing with optically pure silybin diastereomers may suggest new mechanisms of its action.
Keywords: Silymarin/Silybin/ Anticancer activity/P-glycoprotein/Receptors